Climate Change Impact and Trends Analysis of Streamflow at Different Gauging Stations in Upper Jhelum River Basin, Jammu and Kashmir - Mishra , A. K.; Pandit , B. A.; Dadhich , Sushmita M.; Pandey , Yogesh (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
This chapter discusses about the trends analysis of streamflow at different gauging stations in upper jhelum river basin. Water resources of the planet Earth take part in the infinitely recurrent hydrological cycle, the largest movement of matter in the Earth's system. Since water is the basic element of the life support system of the planet, it is of utmost importance to understand the impacts of the ongoing and projected climate change on water resources and water availability. In addition to the study of water resource management, stream flow trend analysis is important for flood forecasting and hydrologic drought assessment related investigations. The long-term changes in stream flow at various gauging stations in the Upper Jhelum River Basin (UJRB) of the Indian state of Jammu and Kashmir (J & K) were estimated in this study. Trend analysis was performed using the Modified Mann-Kendall Test (MMKT). Sen’s Slope Estimator (SSE) was used for the quantification of trend. Long term time series data of annual maximum and monthly maximum stream flows at ten gauging stations of UJRB were used for trend analysis. The annual timeseries of streamflow did not show any significant increasing or decreasing trends at any gauging station. However, all the significant trends obtained at some gauging stations during different seasons were found to be decreasing in nature. Six gauging stations exhibited decreasing streamflow trends during the month of July. Nonetheless, such investigation of water flow in the river would also assist in regional hydrologic studies besides occurrence of flood and hydrologic droughts.